The knowledge base for fisheries management (Elsevier, 2006)
This book describes the state-of-the-art knowledge about fishery systems. Seldom seen in a scientific publication regarding fisheries science, this book presents a multidisciplinary perspective of fisheries management. Leading fisheries scholars with backgrounds in biology, ecology, economics and sociology ask how management institutions can learn and put their lessons to use. The Knowledge Base for Fisheries Management offers a unique overview of the world of fisheries management and provides the background to draw conclusions of what is needed to improve management